Prenatal Substance Exposure and Obesity: Trajectories of Tri-Ponderal Mass Index in Early Adolescence - Li, Ru; Wigley, Isabella Mariani; Suuronen, Ilkka; Jolly, Ashmeet; Tuulari, Jetro J (Elsevier, 2026)
Introduction: The long-term impact of prenatal substance exposure (PSE) on obesity remains inconclusive. Few studies have explored the trajectories of Tri-Ponderal Mass Index (TMI), despite its greater accuracy and reliability in assessing adolescent adiposity. The aim of this study was to examine adiposity trajectories assessed by TMI from pre- to early adolescence and the influence of PSE on these patterns.
Methods: This study used data from the Adolescent Brain Cognitive Development (ABCD) Study (Release 5.1), an ongoing longitudinal study on child development. Data were collected between 2016 and 2021. A total of 7,881 children with data across five waves were included. PSE (tobacco, alcohol, caffeine, marijuana) was reported by mothers. Latent growth mixture modeling was conducted to identify TMI trajectories, followed by multinomial logistic regression to examine the role of PSE, controlling for covariates. All analyses were conducted in 2024.
Results: Three trajectories emerged: Stable TMI (86.6%), Increasing TMI (12.5%), and Decreasing TMI (0.9%). The risk of Increasing TMI was associated with prenatal tobacco and caffeine exposure, showing dose-dependent effects. Tobacco exposure both before and after awareness of pregnancy increased the risk, with no significant benefit from cessation. Prenatal exposure to multiple substances further elevated the risk of Increasing TMI.
Conclusions: Obesity risk can originate prenatally. The long-term impact of prenatal substance exposure on adiposity development during adolescence highlights the need for preconception and prenatal health interventions to reduce obesity risk in offspring.